Підготовка майбутніх фахівців з адаптивного фізичного виховання до роботи у центрах інваспорту з позиції потреб сучасності - Томащук, Олена Григорівна; Деделюк, Ніна Автономівна; Tomashchuk, Olena H.; Dedeliuk, Nina A. (Національний педагогічний університет імені М.П. Драгоманова, 2015)
У статті на основі аналізу психолого-педагогічної літератури й результатів анкетування студентів, щодо наявності у майбутніх фахівців з адаптивного фізичного виховання професійних знань та вмінь, висвітлено зміст та ефективні форми і методи професійної підготовки майбутніх фахівців з адаптивного фізичного виховання до роботи у центрах інваспорту. In the article the content and effective forms and methods of training of future specialists in adaptive physical education to work in the centers invalid sport were highlighted. It was achieved on the basis of analysis of psychological and educational literature, the results of the students questionnaire about the professional knowledge and skills of future specialists in adaptive physical education. The relevance of the investigated problem is caused by the need to overcome the contradictions that arise between the modern requirements for quality of students training and the level of specialists competence in adaptive physical education, that are able to carry out their activities in the centers of invalid sport. It was discussed the difference of the integrity system of professional tasks, that are solved by specialist in adaptive physical education in centers of invalid sport in such spheres, as educational, sports, recreational work and the fragmentary study of all these aspects. The information presented in this article also stresses at the objective necessity for creation a new generation of highly skilled professionals that are ready to work in the centers of invalid sport and insufficient development of students training in different educational levels, that should take into account their individual capabilities, interests and requests for future careers. The purpose of the article was to analyze the results of the students questionnaire about the professional knowledge and skills of future specialists in adaptive physical education and to identify the ways to improve the efficiency of future specialists in adaptive physical education training according to the conditions of work in the invalid sport centers.
The training of future specialists in adaptive physical education to work in the centres of invalid sport according to the current requirements.
Keywords: професійна підготовка; майбутні фахівці з адаптивного фізичного вихованн; центри інваспорту; professional training; future specialists in adaptive physical education; centers of invalid sport